2015
DOI: 10.1175/jcli-d-14-00435.1
|View full text |Cite
|
Sign up to set email alerts
|

Satellite and Argo Observed Surface Salinity Variations in the Tropical Indian Ocean and Their Association with the Indian Ocean Dipole Mode

Abstract: This study investigates sea surface salinity (SSS) variations in the tropical Indian Ocean (IO) using the Aquarius/Satelite de Aplicaciones Cientificas-D (SAC-D) and the Soil Moisture and Ocean Salinity (SMOS) satellite data and the Argo observations during July 2010-July 2014. Compared to the Argo observations, the satellite datasets generally provide SSS maps with higher space-time resolution, particularly in the regions where Argo floats are sparse. Both Aquarius and SMOS well captured the SSS variations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 68 publications
2
60
1
Order By: Relevance
“…Figure 6b shows the global averages of regional temporal STD values of Aquarius SSS with respect to Argo-SIO SSS for various spatial scales. The difference between Figure 6a [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1 • × 1 • scale and 0.04 psu for 10 • × 10 • scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonalmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure 6b shows the global averages of regional temporal STD values of Aquarius SSS with respect to Argo-SIO SSS for various spatial scales. The difference between Figure 6a [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1 • × 1 • scale and 0.04 psu for 10 • × 10 • scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonalmentioning
confidence: 87%
“…Figure 6c,d shows the global average of STD values for composite seasonal anomalies and nonseasonal anomalies (referenced to the composite seasonal cycle) of the SSS differences between Aquarius and Argo-SIO. The non-seasonal anomalies are associated with the differences between Aquarius and Argo-SIO in representing non-seasonal signals associated with phenomena such as tropical instability waves [4,21], Madden-Julian Oscillation [22,23], El Niño-Southern Oscillation [24], and Indian Ocean Dipole [25]. It is noteworthy that the global average STD value for non-seasonal SSS anomalies is less than 0.1 psu for 1° × 1° scale and 0.04 psu for 10° × 10° scale.…”
Section: Quantification Of the Time-mean Seasonal And Non-seasonalmentioning
confidence: 99%
“…Interannual and decadal variations of the SSS are to a large extent forced by air‐sea freshwater fluxes, with additional contributions from ocean dynamics such as advection, entrainment and diffusion [ Rao and Sivakumar , ; Ren et al ., 2009, ]. Interannual salinity variability in the Equatorial Indian Ocean (EIO) has been demonstrated to be closely related to the Indian Ocean Dipole (IOD) [ Grunseich et al ., ; Zhang et al ., ; Nyadjro and Subrahmanyam , ; Du and Zhang , ], an important interannual climate mode in the IO [ Saji and Yamagata , ]. Besides IOD, ENSO is another prominent interannual mode that affects the coupled ocean‐atmosphere processes in the IO [ Schott et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…In the tropical IO, the Indian Ocean dipole (IOD) is associated with sea surface temperature (SST), cooling off the Java‐Lesser Sunda coast and warming in the western tropical IO during the positive IOD events, and vice versa for the negative IOD events (Du et al, ; Saji et al, ; Webster et al, ; Yamagata et al, ). Noticeable interannual‐decadal variability of salinity in the tropical IO, which is closely related to the IOD and Walker Circulation variability, has been documented by recent Argo and satellite observations (Du et al, ; Du & Zhang, ; Grunseich et al, ; Nyadjro & Subrahmanyam, ). It was reported that negative SSS anomalies appear near the equator and positive SSS anomalies appear in the southeastern IO during the positive IOD events, and vice versa during the negative IOD events (Masson et al, ; Thompson et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 66%
“…Previous studies mainly focused on salinity variability and its relationship with precipitation and ocean processes in the tropical IO. The anomalous equatorial currents, attributed to anomalous easterly winds, lead to low‐SSS anomaly along the equator, while in the southeastern IO enhanced coastal upwelling and the freshwater flux are crucial to the SSS anomaly during the developing and mature phases of the IOD events (Du & Zhang, ; Nyadjro & Subrahmanyam, ; Vinayachandran & Nanjundiah, ; Zhang et al, ). In addition, the SSS variability is important during the decay phase and the following year of IOD events in the southern tropical IO where circulation system plays a significant role in maintaining the heat and salt balance of the entire area, including the Wyrtki Jets (WJs; Wyrtki, ) and the south equatorial current (SEC).…”
Section: Introductionmentioning
confidence: 99%